Regulation of Hemoglobin β-Chain Synthesis in Bone Marrow Erythroid Cells by α Chains - Wolf, Jeffrey L. (1973)
Synthesis of α and β chains of hemoglobin was studied in vitro in intact reticulocytes and bone marrow cells. The cells were from rabbits having a variant form of hemoglobin in which L-isoleucine is in the α but not in the β chains. This characteristic permitted a selective inhibition of α-chain synthesis to be produced by addition to the incubation medium of L-O-methylthreonine, an inhibitor of protein synthesis that is a specific antagonist of L-isoleucine. In studies with reticulocytes, 25 mM L-O-methylthreonine produced a 60-70% inhibition of α-chain synthesis, but β-chain synthesis was unaffected even after incubation times for 4 hr. Because reticulocytes contain a pool of uncombined α chains which might have obscured the demonstration of an α chain-dependent mechanism for β-chain synthesis, subsequent studies were done with bone marrow cells. The latter had little or no detectable α-chain pool. A substantial inhibition of α-chain synthesis by the bone marrow cells was produced by the isoleucine antagonist but was also accompanied by a significantly decreased rate of β-chain synthesis. These findings suggest that the coordinated synthesis of the complementary α- and β-globin chains of hemoglobin may reflect in part a modifying effect of α-chain synthesis on the synthesis of β chains.